Intact IGF-binding protein-4 and -5 and their respective fragments isolated from chronic renal failure serum differentially modulate IGF-I actions in cultured growth plate chondrocytes - Choukair, Daniela; Andress, Dennis L.; Mohan, Subburaman; Ständker, Ludger; Ulinski, Tim; Himmele, Rainer; Mehls, Otto; Tönshoff, Burkhard (Journal of the American Society of Nephrology, 2001)
Abstract. Impairment of longitudinal growth among children with chronic renal failure (CRF) may be partly attributable to the inhibition of insulin-like growth factor (IGF) activity by an excess amount of high-affinity IGF-binding proteins (IGFBP). Elevated levels of immunoreactive IGFBP-4 in CRF serum are inversely correlated with the standardized heights of these children, whereas levels of IGFBP-5, which circulates mainly as proteolyzed fragments, are positively correlated with growth parameters. To delineate the respective effects of these IGFBP on growth cartilage, the biologic effects of intact and fragmented forms of IGFBP-4 and IGFBP-5 on rat growth plate chondrocytes in primary cultures were characterized. Intact IGFBP-4 and IGFBP-5 and the amino-terminal fragment IGFBP-51-169 were recombinant proteins; the carboxy-terminal fragments IGFBP-5144-252 and IGFBP-4136-237 and the amino-terminal fragment IGFBP-41-122 were purified to homogeneity from CRF hemofiltrates. Intact IGFBP-4 and, to a lesser extent, IGFBP-41-122 inhibited IGF-I-induced cell proliferation. In contrast, intact IGFBP-5 was stimulatory in the absence or presence of exogenous IGF-I, whereas the amino-terminal fragment IGFBP-51-169 was inhibitory. Studies on the mechanism by which IGFBP-4 and IGFBP-5 exert opposite effects on chondrocyte proliferation demonstrated that intact IGFBP-4 prevented the binding of 125I-IGF-I to chondrocytes, whereas intact IGFBP-5 enhanced ligand binding and was able to bind specifically to the cell membrane. These data suggest that intact IGFBP-4 and, to a lesser extent, IGFBP-41-122 act exclusively as growth-inhibitory binding proteins in the growth cartilage. IGFBP-5, however, can either stimulate (if it remains intact) or inhibit (if amino-terminal forms predominate) IGF-I-stimulated chondrocyte proliferation.